2011
DOI: 10.1590/s0100-84042011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, morphological and biochemical characteristics of the sexual propagation of Piper aduncum (Piperaceae)

Abstract: -(Physiological, morphological and biochemical characteristics of the sexual propagation of Piper aduncum (Piperaceae)). In this work we attempted to characterize the diaspores and the germination process of Piper aduncum L., as well as to verify the influence of the interaction between presence and absence of light (photoperiod of 12 hours and dark) and temperature (25 °C, 30 °C and 20-30 °C) and also of gibberellin (0, 50, 100, 200 and 400 mg L -1 ) on the root protrusion and normal seedlings formation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Dormancy in seeds of this species has neither been reported in literature, nor found in this study. In this study P. aduncum had a maximum germination percentage above 80% in all experiments, which was immediate compared with previous reports (Rocha et al ., ; Silva et al ., ; Dousseau et al ., ). Our results showed that P. aduncum seeds failed to germinate at temperatures above 35°C (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dormancy in seeds of this species has neither been reported in literature, nor found in this study. In this study P. aduncum had a maximum germination percentage above 80% in all experiments, which was immediate compared with previous reports (Rocha et al ., ; Silva et al ., ; Dousseau et al ., ). Our results showed that P. aduncum seeds failed to germinate at temperatures above 35°C (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…These habitats are usually characterised by high light intensity and enhanced fluctuations in temperature and water availability. High light intensity favours the germination of P. aduncum seeds, which are positively photoblastic and do not germinate in the dark (Rocha et al ., ; Dousseau et al ., ), but how seeds of this species respond to high temperature and water restriction remains unknown. The study reported here investigated the responses of P. aduncum seed germination to temperature and water potential, with the intention of improving our understanding of its advantages and limitations as an invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…Both Mexican sunflower and bamboo piper are native to Mexico and Central America, and have become plant invaders in Xishuangbanna. As invasive species, they are both prolific seed producers, with the capability to produce small but numerous viable seeds every year, have rapid growth, high rates of biomass accumulation, a short juvenile period and high reproductive efforts [ 2 , 7 , 20 22 ], all attributes which are thought to contribute to invasiveness [ 19 , 23 , 24 ]. On the other hand, deforestation and habitat disturbance in this area in past decades [ 25 ] increased resource availability for these invaders, for these changed biotic and abiotic conditions [ 26 30 ], and are widely recognized as a primary influence to make the habitat more susceptible to invasion, or even become a crucial driver of invasion [ 31 – 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, deforestation and habitat disturbance in this area in past decades [ 25 ] increased resource availability for these invaders, for these changed biotic and abiotic conditions [ 26 30 ], and are widely recognized as a primary influence to make the habitat more susceptible to invasion, or even become a crucial driver of invasion [ 31 – 35 ]. Although its seeds are small and strict positively photoblastic [ 20 ], bamboo piper dominates only relatively cool and wet habitats like forest ridges and remains an intermediate invader in Xishuangbanna [ 8 ] while Mexican sunflower can colonize bare ground and form monospecific stands, and demonstrates stronger invasiveness in this area [ 4 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positive correlation of percent of germination also was shown for Clausena excavata Burm. f. (Vieira et al 2010), Piper aduncum L. (Rocha et al 2005;Dousseau et al 2011), Crassocephalum crepioides (Benth.) S. Moore, Ageratum conyzioides L. (Yuan & Wen 2018), Rumex confertus L. (Kołodziejek & Patykowski 2015) and numerous other invasive plant species.…”
Section: Discussionmentioning
confidence: 99%